Proceedings of the 33rd SIGCSE Technical Symposium on Computer Science Education 2002
DOI: 10.1145/563340.563345
|View full text |Cite
|
Sign up to set email alerts
|

A case study of LEGO Mindstorms'™ suitability for artificial intelligence and robotics courses at the college level

Abstract: This paper examines LEGO Mindstorms 'TM suitability as a hardware platform for integrating robotics into an Artificial Intelligence course organized around the agent paradigm popularized by Russell and Norvig. This evaluation discusses how kits and projects based on Mindstorms supported students' exploration of the issues behind the design of agents from three classes in Russell and Norvig's intelligent agent taxonomy. The paper's investigation also examines several popularly-perceived limitations of the Minds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 3 publications
0
23
0
1
Order By: Relevance
“…We deliberately chose a fully assembled approach as opposed to build-your-own kits such as the Lego Mindstorms TM because previous work has shown that even advanced computer science students feel that they spend too much time on the "design of robot chassis" when using Mindstorms TM [8]. Because we are not teaching a multidisciplinary class such as that by Weinberg et al [16], presenting students with a fully assembled robot removes the unnecessary complications of mechanical assembly, allowing them to focus on computer science concepts.…”
Section: The Robot Kitmentioning
confidence: 99%
“…We deliberately chose a fully assembled approach as opposed to build-your-own kits such as the Lego Mindstorms TM because previous work has shown that even advanced computer science students feel that they spend too much time on the "design of robot chassis" when using Mindstorms TM [8]. Because we are not teaching a multidisciplinary class such as that by Weinberg et al [16], presenting students with a fully assembled robot removes the unnecessary complications of mechanical assembly, allowing them to focus on computer science concepts.…”
Section: The Robot Kitmentioning
confidence: 99%
“…It is also possible to extend the range of tasks by using a more sophisticated programming language. BrickOS , BrickOS 2004] provides a more complete version of C than NQC, and one can also program the Mindstorms in Java [Laverde et al 2002] and Lisp [Klassner 2002;Klassner and Anderson 2003]. …”
Section: Course Structurementioning
confidence: 99%
“…Although the MindStorms kit is a wonderful way to teach students about robotics, it is limited to a dry environment, such as class room floor. For the past decade, the MindStorms have been used in computer science resources to teach concepts from object-oriented programming (Barnes D., 2002) to artificial intelligence (Klassner F., 2002). They have been used to introduce students to the exciting world of computers (Weisheit F., 2004).…”
Section: Introductionmentioning
confidence: 99%